Lower-leg compression, running mechanics, and economy in trained distance runners - Stickford, A. S. L.; Chapman, R. F.; Johnston, J. D.; Stager, J. M. (International Journal of Sports Physiology and Performance, 2015)
The efficacy of and mechanisms behind the widespread use of lower-leg compression as an ergogenic aid to improve running performance are unknown. The purpose of this study was to examine whether wearing graduated lower-leg compression sleeves during exercise evokes changes in running economy (RE), perhaps due to altered gait mechanics. Sixteen highly trained male distance runners completed 2 separate RE tests during a single laboratory session, including a randomized-treatment trial of graduated calf-compression sleeves (CS; 15-20 mm Hg) and a control trial (CON) without compression sleeves. RE was determined by measuring oxygen consumption at 3 constant submaximal speeds of 233, 268, and 300 m/min on a treadmill. Running mechanics were measured during the last 30 s of each 4-min stage of the RE test via wireless triaxial 10-g accelerometer devices attached to the top of each shoe. Ground-contact time, swing time, step frequency, and step length were determined from accelerometric output corresponding to foot-strike and toe-off events. Gait variability was calculated as the standard deviation of a given gait variable for an individual during the last 30 s of each stage. There were no differences in VO2 or kinematic variables between CON and CS trials at any of the speeds. Wearing lower-leg compression does not alter the energetics of running at submaximal speeds through changes in running mechanics or other means. However, it appears that the individual response to wearing lower-leg compression varies greatly and warrants further examination.